IMPLEMENTASI APLIKASI ZEP QUIZ DALAM PERENCANAAN KARIR SISWA - Mulyawan, Galuh; Ramanda, Peni; Damayanti, Sabrina Yunita; Jannah, Ratu Roudlotul (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to test the effectiveness and implement the Zep Quiz application as a tool to improve the understanding and career planning of 10th grade students of Senior High School (SMA). Career planning in early adolescence is an important stage in directing students towards future education and job choices. The Zep Quiz application is designed to provide an interactive questionnaire that can identify students' interests and talents, as well as provide relevant career recommendations. The research method used is a quasi-experimental with a one-group pretest-posttest design of 30 10th grade students from one of the senior high schools in Cilegon. Data were collected through a career planning questionnaire given before (pretest) and after (posttest) the intervention using the Zep Quiz application. The results showed a significant increase in students' career planning scores after participating in the Zep Quiz intervention. The implication of this study is that the Zep Quiz application can be an effective tool in facilitating students' career planning at the senior high school level.